THE USE OF TEACHING READING COMPREHENSION THROUGH QUESTION GENERATION STRATEGY - Kholifuddin Roma; Yusawinur Barella (Universitas Tanjungpura, 2022)
This study aimed to explore a question generation strategy for teaching reading comprehension. It was quasi-experimental. The research population used in this study was the whole ninth-grade students of SMP Walisongo Pontianak in the academic year of 2021/2020. This study utilized cluster random sampling to take and choose the sample. The samples were the students from B Class becoming the experimental group and D Class becoming the control group. It applied the measurement technique in this study. The tool of the data collection was a reading test. This study analyzed the data obtained through an independent samples test. The research result showed that the Sig value < 0.05 (0.004 < 0.05), meaning Ha accepted. It proved that the question generation strategy could increase the students’ reading comprehension and make them actively motivated and involved in the learning process. Besides, the significant effect in teaching reading comprehension had a strong effect (0.727). Therefore, it is proposed to use in teaching the reading comprehension context. It could develop students’ thoughts about understanding the text, encourage them to be active and smart readers, increase their understanding of the text they read, and help them catch essential ideas.